Foreign Direct Investment in Romania Before, during and after the Coronavirus Pandemic - Hagiu, Alina; Barbulescu, Marinela (Journal of Danubian Studies and Research, 2022)
Foreign direct investment plays an extremely important role in the Romanian economy. If in 1990 the Romanian economy registered a low productivity and competitiveness, today it looks completely different. Romania has competitive sectors at regional and even global level, has been integrated into international production chains and exports high quality products. These things would not have been possible without the foreign capital that contributed funding and know-how and helped Romania to enhance its competitive advantages and well-trained workforce. In this paper we aim to make a retrospective of foreign direct investment in Romania before and after the coronavirus pandemic if we can consider it completed and identify the most attractive regions for investment in Romania..